(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the results of chorionic villus sampling (CVS) in cases with single-gene mutations at Hanoi Obstetrics and Gynecology Hospital from 2022 to 2024. Subjects and Methods: A retrospective descriptive cross-sectional study was conducted on 5 pregnant women with suspected pathological single-gene genetic abnormalities who were indicated for CVS, including 53 cases in which one or both partners had previously been identified as carriers of pathogenic genes and 3 cases in which the pregnant women had not been previously identified as carriers of pathogenic genes. Results: The majority of pregnant women in the study group were aged 20–34 years (89%). CVS was performed between 11 and 14 weeks of gestation, most commonly at 12 and 13 weeks. Fourteen cases were indicated for pregnancy termination due to the presence of pathogenic genotypes. Conclusion: CVS is an invasive prenatal diagnostic technique that enables early detection of inherited pathogenic single-gene disorders (from 11 to 14 weeks of gestation).